Links between Autism Spectrum Disorder Diagnostic Status and Family Quality of Life - Andrew G. McKechanie; Vivien J. Moffat; Eve C. Johnstone; Sue Fletcher-Watson (MDPI AG, 2017)
Quality of life is often relatively lowered in families of children with additional needs, and this may be particularly the case where additional needs are accompanied by an autism spectrum disorder (ASD). Here we explore the effects of diagnostic status specifically, comparing families with children with an ASD diagnosis with others who a) have additional needs but no signs of ASD; and b) have additional needs and signs of ASD but no diagnosis. Mothers (n = 76) of children with additional needs completed standardised questionnaires about quality of life, stress, service provision, child behaviour and presence and severity of ASD traits. In addition, a group of mothers of typically developing young people (n = 17) completed standardised questionnaires on individual and family quality of life and on the behaviour of their son or daughter. Mothers of typically developing young people had significantly higher individual and family quality of life scores than each of the three other groups. Increased severity of ASD was associated with increased maternal stress, which in turn was associated with decreased family and maternal quality of life. The group reporting the lowest quality of life and the highest stress were the mothers of individuals with signs of ASD but no diagnosis. This pattern did not seem to be explained by lack of access to services, or rates of intellectual disability or challenging behaviour in this sub‐group. The finding that poor quality of life and high stress was most apparent in the sub‐group of mothers with children who had signs of ASD but did not have a diagnosis of ASD suggests that an interesting topic for further investigation is whether receipt of a diagnosis itself can positively influence quality of life and levels of maternal stress.